(untitled) (Indian Journal of Arid Horticulture, 2025)
An experiment was conducted at College of Agriculture, Bikaner to find out the effect of improved cultivation practices viz., irrigation methods, planting of different cultivars and uses of mulches on incidence of jassid (Amrasca biguttula biguttula) in okra. The results of the experiment revealed that in case of irrigation methods, the minimum number of jassid (1.73/3 leaves) was recorded in 0.6 volume of drip irrigation while maximum (5.45/ 3 leaves) was observed in 1.0 volume of surface irrigation. Planting of different cultivar was not significantly influence the incidence of jassid. In the treatments when mulches were used, this minimum number of jassid (2.69/ 3 leaves) was recorded in bui mulch while maximum number of jassid was recorded in those treatments when mulches were not used.